Transthyretin Stabilizers and Seeding Inhibitors as Therapies for Amyloid Transthyretin Cardiomyopathy - Paolo Morfino; Alberto Aimo; Giuseppe Vergaro; Chiara Sanguinetti; Vincenzo Castiglione; Maria Franzini; Marco Alfonso Perrone; Michele Emdin (MDPI AG, 2023)
Transthyretin (TTR) amyloid cardiomyopathy (ATTR-CM) is a progressive and increasingly recognized cause of heart failure which is associated with high mortality and morbidity. ATTR-CM is characterized by the misfolding of TTR monomers and their deposition within the myocardium as amyloid fibrils. The standard of care for ATTR-CM consists of TTR-stabilizing ligands, such as tafamidis, which aim at maintaining the native structure of TTR tetramers, thus preventing amyloid aggregation. However, their efficacy in advanced-staged disease and after long-term treatment is still a source of concern, suggesting the existence of other pathogenetic factors. Indeed, pre-formed fibrils present in the tissue can further accelerate amyloid aggregation in a self-propagating process known as "amyloid seeding". The inhibition of amyloidogenesis through TTR stabilizers combined with anti-seeding peptides may represent a novel strategy with additional benefits over current therapies. Finally, the role of stabilizing ligands needs to be reassessed in view of the promising results derived from trials which have evaluated alternative strategies, such as TTR silencers and immunological amyloid disruptors.